Pengaruh Celebrity Endorsement terhadap Keputusan Pembelian pada Produk Fashion Tsaqawa (Survey pada Akun Instagram @Rachelvennya) - Fadhilah, Ninda Nurul; Zulfa, Milatul; Harjono, Muhammad Budi; Wirayuda, Dimas (TAMADDUN: Jurnal Ilmu Sosial, Seni, dan Humaniora, 2025)
The use of celebrity endorsement is an effective strategy in digital marketing communication to attract attention and shape consumer attitudes. This study examines the effect of celebrity endorsement @rachelvennya on purchasing decisions for Tsaqawa Official fashion products. Using a quantitative approach with an explanatory research type, data was collected through a survey of 100 respondents. The results of the analysis show that celebrity endorsement has a positive and significant effect on purchasing decisions, as evidenced by a significance value of 0.000 <0.05 and a correlation of 0.876. This research applies AIDA theory, source credibility theory, and Integrated Marketing Communication (IMC) concepts to understand the mechanism of influence. The Respondent Achievement Rate (TCR) on the perception of Rachel Vennya's celebrity endorsement is also in the good category. These findings reinforce that celebrity endorsements can increase attention, interest, desire, and drive purchasing decisions, while building a strong emotional connection between brands and consumers, especially on social media platforms such as Instagram.